Homocysteine, HHcy, H-type hypertension and dizziness: an NHANES analysis - Yiyin Liang; Tianjie Lai; Juan Feng (Frontiers in Neurology)
BackgroundHomocysteine (Hcy) is associated with various diseases, but its specific relationship with different types of dizziness remains unclear.ObjectivesThis study utilizes NHANES cross-sectional data to investigate the associations between Hcy levels, H-type hypertension, and various symptomatic dizziness, aiming to provide new insights for clinical diagnosis and treatment.Materials and methodsThis cross-sectional study analyzed 6,970 participants from NHANES (1999–2004) using weighted logistic regression, trend tests, restricted cubic spline analysis, and subgroup analysis.ResultsElevated Hcy levels and H-type hypertension showed significant positive associations with various symptomatic dizziness. HHcy showed the strongest association with fall risk (OR = 1.83, 95% CI: 1.24–2.77), while H-type hypertension was most strongly associated with any symptomatic dizziness (OR = 1.75, 95% CI: 1.34–2.28). No significant associations were found with positional dizziness. Trend analysis indicated a significant upward trend in the risk of any symptomatic dizziness, balance problems, and falling problems. RCS analysis demonstrated non-linear relationships between Hcy levels and various symptomatic dizziness, including any symptomatic dizziness, balance problems, and falling problems.Conclusions and significanceThis study revealed that Hcy levels, HHcy, and H-type hypertension were significantly associated with various symptomatic dizziness. Recognizing and controlling HHcy and H-type hypertension are vital for dizziness management and diagnosis.